Comment on "Younger Dryas sea level and meltwater pulse 1B recorded in Barbados reefal crest coral Acropora palmata" by N. A. Abdul et al. (20th December 2016) - Bard, Edouard; Hamelin, Bruno; Deschamps, Pierre; Camoin, Gilbert
Abstract: Based on new U‐Th ages of corals drilled offshore Barbados, Abdul et al. (2016) have confirmed the existence of the abrupt stratigraphic feature called meltwater pulse 1B (MWP‐1B), which they interpret as being due to a very large and global sea level step change dated at about 11.3 kyr before present (approximately 15 m and equivalent to twice the amount of water stored in the present Greenland ice sheet). This contrasts with the Tahiti record, in which MWP‐1B is essentially absent or very small, as Carlson and Clark (2012) and Lambeck et al. (2014) also conclude in their recent reviews of deglacial sea levels at the global scale. However, the evidence provided by Abdul et al. and their main conclusions are not convincing as they are affected by the following three main problems, which may explain the apparent discrepancies: Problem #1/Barbados is located in a subduction zone, which was also active throughout the Late Glacial period. Furthermore, the Barbados cores studied by Abdul et al. were drilled on both sides of the extension of a tectonic feature identified at the southern tip of Barbados (South Point) as underlined by several studies of the Barbados stratigraphy. Problem #2/Fossil samples of Acropora palmata may not be reliable sea level markers during rapid and large sea level rises. Indeed, the asexual reproduction strategy of this species may not be optimal to keep up when the water depth is increasing very rapidly. This may in part explain why the living depth of A. palmata at Barbados was significantly greater than 5 m during some periods of the last deglaciation, notably between 14.5 and 14 kyr B.P. and possibly between 14 and 11.5 kyr B.P. Problem #3/The slow glacio‐isostatic adjustment and the rapid responses due to gravitational changes of ice and water masses complicate the interpretation of individual relative sea level (RSL) records at specific locations. Therefore, the Barbados and Tahiti record cannot be compared directly in terms of absolute sea level values as done by Abdul et al. In addition, different glaciohydroisostatic adjustments at the two sites may also have contributed to the observed discrepancy between their deglacial RSL records. Key Points: MWP‐1B at approximately 11.3 kyr B.P. may partly be an artifact of Barbados tectonics linked to the proximity of an active subduction zone Fossil samples of Acropora palmata may not be reliable sea level markers during rapid and large sea level rises Glacio‐hydro‐isostatic adjustments may have also contributed to the observed discrepancy between the Barbados and Tahiti deglacial records